2017
DOI: 10.1111/medu.13266
|View full text |Cite
|
Sign up to set email alerts
|

The economic cost of failure in clinical education: a multi-perspective analysis

Abstract: Strong economic links for multiple stakeholders as a result of failure by students in clinical education have been identified. The cost burden is skewed in the direction of students. Any generalisation of these results should be made with consideration for the unique clinical education context in which each health professional education programme operates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…This is only partly influenced by SES. In any case, it must be recognized that there are costs associated with failing students in a selection system (or a student may 'luck out' in a lottery system, Foo et al, 2017). Further downstream in specialty training, there is a scarcity of data around diversity with the exception of evidencing independent predictors of rural medical practice, where there is a strong positive correlation between rural background and rural clinical school exposure (Farmer, Kenny, McKinstry, & Huysmans, 2015) suggesting there needs to be greater integration of selection with policy.…”
Section: (3) Diversity and Globalisation Issuesmentioning
confidence: 99%
“…This is only partly influenced by SES. In any case, it must be recognized that there are costs associated with failing students in a selection system (or a student may 'luck out' in a lottery system, Foo et al, 2017). Further downstream in specialty training, there is a scarcity of data around diversity with the exception of evidencing independent predictors of rural medical practice, where there is a strong positive correlation between rural background and rural clinical school exposure (Farmer, Kenny, McKinstry, & Huysmans, 2015) suggesting there needs to be greater integration of selection with policy.…”
Section: (3) Diversity and Globalisation Issuesmentioning
confidence: 99%
“…4 Cost evaluation represents a promising opportunity to determine the value of programmes of assessment or learning. In this issue, Foo et al 5 examined this problem by estimating what failure in health professions education costs different stakeholders, including government, students and educational institutions. We would like to extend their discussion by highlighting additional considerations for the study of cost.…”
Section: Martin G Tolsgaard 1 and David A Cookmentioning
confidence: 99%
“…11 We suspect that in many cases, cost will vary across contexts even more than other education outcomes. Foo et al 5 address the issue of context directly in an exemplary manner.…”
Section: Martin G Tolsgaard 1 and David A Cookmentioning
confidence: 99%
“…Characteristically, this and other Australian costing studies were undertaken from the placement providers' perspective and focussed on the degree of productivity gains/losses experienced by providers of TCP. While authors of some studies found gains in productivity (Dillon, Tomaka, Chriss, Gutierrez & Hairston, 2003;Leiken, Stern & Baines, 1983;Rodger, Stephens, Clark, Ash & Graves, 2011;Rodger et al, 2012), others estimated substantial losses (Bowles et al, 2014;Foo et al, 2017;Jones & Akehurst, 1999). Unfortunately differences in methodological frameworks prevented a meaningful comparison of the published results.…”
Section: Introductionmentioning
confidence: 99%
“…Our literature search identified publications that adopted a multi-stakeholder perspective (Haines, Kent & Keating, 2014;Lalloo & Massey, 2013), but only one specifically focussed on allied health students, albeit only those who failed their clinical education (Foo et al, 2017). None of the economic evaluations were conducted alongside an RCT or involved an SCP as one of the evaluated alternatives.…”
Section: Introductionmentioning
confidence: 99%